THE GATEKEEPERS OF RURAL DEMOCRACY: RELIGIOUS AND TRADITIONAL LEADERS AS POLITICAL OPINION MAKERS - Prasetya Yoga Santoso (AKSELERASI: Jurnal Ilmiah Nasional, 2023)
This study aims to analyze the role of religious and traditional leaders as opinion leaders in the dynamics of rural political communication, using a case study in Sirnaresmi Village, Cisolok District, Sukabumi Regency, West Java Province (Kasepuhan Ciptagelar). This qualitative case study employed a purposive sampling technique to identify key informants, including traditional elders, religious scholars, village officials, and the local community. Data were collected through participant observation, in-depth interviews, and documentation studies, which were then analyzed using the Miles and Huberman interactive model. The results indicate that the flow of political communication in this village consistently applies the Two-Step Flow Theory mechanism, in which external political information is first filtered by opinion leaders before being disseminated to the community. The dualistic authority structure in this village does not give rise to conflict, but rather produces a convergence of complementary communication; religious leaders mobilize the masses based on moral-theological persuasion through the religious study group (Majelis Taklim), while traditional leaders use communal-cultural persuasion through traditional institutions to maintain village stability. This integrative-collective opinion leadership model has proven effective in reducing electoral polarization, countering digital disinformation, and significantly increasing voter participation. This study concludes that the effectiveness of political communication in rural areas depends heavily on the level of sociological trust in local actors, whose position remains unchallenged by the massive development of modern media.